2022
DOI: 10.12659/ajcr.935016
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Lymphatic Injuries After Suction Lipectomy in Women with Lipedema

Abstract: Case series Patients: Female, 55-year-old • Female, 38-year-old • Female, 62-year-old Final Diagnosis: Lymphedema Symptoms: Skin fibrosis • swelling Medication: — Clinical Procedure: Liposuction and lipofilling • suction lipectomy Specialty: Dermatology • Plastic Surgery • Surgery Objective: Unusual clinical course Background: Lipedema is a loose connective tissue disease characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…7 Despite the concern of possible lymphatic damage due to surgical trauma, only one case series was found that described lymphatic injuries in three lipedema patients after SAL. 8 Strong evidence supports that, when performed by an experienced team, tumescent liposuction can improve quality of life with lymphatic safety. 3,4,9 Notwithstanding, paucity of data suggests postsurgical lymphatic improvement.…”
Section: Discussionmentioning
confidence: 94%
“…7 Despite the concern of possible lymphatic damage due to surgical trauma, only one case series was found that described lymphatic injuries in three lipedema patients after SAL. 8 Strong evidence supports that, when performed by an experienced team, tumescent liposuction can improve quality of life with lymphatic safety. 3,4,9 Notwithstanding, paucity of data suggests postsurgical lymphatic improvement.…”
Section: Discussionmentioning
confidence: 94%
“…After deduplication and screenings, 20 articles met the inclusion/exclusion criteria. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] ►Fig. 1 provides an overview of the PRISMA process for conducting this systematic review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…16,17 Lymphedema is a comorbidity, 18 and lymphatic injury can occur after liposuction. [19][20][21] Up to 50% of women with lipedema also have venous disease. [22][23][24] In this study, LRS uses suction lipectomy with techniques to protect lymphatic structures and can include manual extraction of fibrous tissues that remain after maximal debulking of tissue.…”
Section: Introductionmentioning
confidence: 99%